Le livre numérique, planche de salut pour la lecture ? - Vincent Chabault (Communication)
Since the 1990s, the apparent decline of readership among the younger generation, especially among students, has been a source of fierce debate and innumerable studies — all too often based on the printed word. Such arguments are today losing all credibility. With the growing number of digital books and increasing virtualization of content, this trend can only accelerate. Can e-books possibly counter the expected demise of the printed word and become catalysts for increased readership among the younger generation and students? After surveying a sample of students, the author provides some answers.